Committing to grow: Employment targets and firm dynamics - Ufuk Akcigit; Harun Alp; André Diegmann; Nicolas Serrano-Velarde (Halle Institute for Economic Research (IWH), 2025)
We examine effects of government-imposed employment targets on firm behavior. Theoretically, such policies create “polarization,“ causing low-productivity firms to exit the market while others temporarily distort their employment upward. Dynamically, firms are incentivized to improve productivity to meet targets. Using novel data from East German firms post-privatization, we find that firms with binding employment targets experienced 25% points higher annual employment growth, a 1.1% points higher annual exit probability, and 10% points higher annual productivity growth over the target period. Structural estimates reveal substantial mis-allocation of labor across firms and that subsidizing productivity growth would yield twice the long term increases in employment.
Keywords: D22; D24; J08; L25; 330; industrial policy; privatizations; productivity; size-dependent regulations; Nationale Einheit; Privatisierung; Industriepolitik; Arbeitsmarktpolitik; Wirkungsanalyse; Beschäftigungseffekt; Produktivitätsentwicklung; Unternehmenserfolg; Endogenes Wachstumsmodell; Ostdeutschland